2001
DOI: 10.1054/bjoc.2000.1600
|View full text |Cite
|
Sign up to set email alerts
|

Ternary combination of irinotecan, fluorouracil-folinic acid and oxaliplatin: results on human colon cancer cell lines

Abstract: Summary A marked antitumour efficacy is currently obtained by oxaliplatin (LOHP)-fluorouracil (FU)-folinic acid (FA) combination and by CPT11-FU-FA combination. Logically, the triple association LOHP, CPT11 and FUFA will be soon tested in cancer patients. The aim of the present study was to compare two schedules combining SN38 (the active metabolite of CPT11, irinotecan) with FU-FA and LOHP. The two schedules differed by the SN38 position. The relative contribution of each drug in the resulting global cytotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 24 publications
3
22
0
2
Order By: Relevance
“…Moreover, our regimen was very active despite this dose reduction. This finding confirms the in-vitro observation, which highlighted the greatest contribution of OXA to the overall cytotoxicity of the triplet combination [19], and suggests that a slight dose reduction of this regimen in further clinical evaluation could not jeopardize its activity.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, our regimen was very active despite this dose reduction. This finding confirms the in-vitro observation, which highlighted the greatest contribution of OXA to the overall cytotoxicity of the triplet combination [19], and suggests that a slight dose reduction of this regimen in further clinical evaluation could not jeopardize its activity.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, an in-vitro study on two human colon cancer cell lines (SW620 and WIDR) reported the interaction of different simultaneous exposures to OXA, SN38 and 5FU modulated by FA (FUFA) [19]. In this study, the OXA + FUFA combination was always synergistic, the OXA + SN38 combination was either additive (when SN38 was applied after OXA) or antagonistic (when SN38 was applied first), SN38 + FUFA was always antagonistic, while the triple exposure (OXA+SN38+FUFA) was additive.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies showed a synergistic activity of the SN-38/L-OHP combination [14] and indicated that the sequence of administration is important. Further in vitro studies investigating combinations of 5-FU, CPT-11, and L-OHP have shown that a synergism occurs only when CPT-11 precedes 5-FU/L-OHP exposure [15].…”
Section: Introductionmentioning
confidence: 99%
“…First, it would be interesting to see if a sequential regimen with FU/leucovorin followed by a combination of irinotecan and oxaliplatin is comparable to concomitant administration of all three drugs [22, 23, 24, 25]. The second question is that the combination tested is extremely interesting for patients that more likely will fail to fluoropyrimidine therapy, according to intratumoral levels of the specific enzymes within the drug’s anabolic and catabolic pathways.…”
Section: Discussionmentioning
confidence: 99%